Random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) primer design for the detection of Listeria monocytogenes - Perez, Maria Teresa M. (Transactions of the National Academy of Science and Technology, 2011)
Listeria monocytogenes is a major foodborne pathogen recognized worldwide by food industries and public safety institutions because of its high fatality rate and various complications such as acute diarrhea, meningoencephalitis, septicaemia, and abortion. USFDA imposes "zero tolerance" regulation for L. monocytogenes in raw and ready-to-eat foods. The National Meat Inspection Services of the Department of Agriculture is strictly monitoring it in processed meat. This study reports on the design of primers through hybridization, cloning and sequencing of RAPD-PCR amplification products identified to be specific for L. monocytogenes reference strains (Lm2, Lm3, and Lm4) against closely related isolates: Listeria spp. ad Enterococcus strains isolated from different food sample at the Food and Feed Laboratory, BIOTECH, UPLB. Gene amplification using RAPD primer 066 resulted in a potential specific 1.2 kb marker. Molecular cloning of the isolated RAPD marker for L.monocytogenes was done to facilitate sequencing of the amplicon. Twenty-three presumptive positie clones were subjected to plasmid DNA extractives and restriction enzyme analysis to determine the presence of the target insert fragment. Two plasmid clones confrimed the presence of the target insert fragment through hybridization. The plasmid clone (5a1) was sequenced using the universal primers, M13. Multiple sequence alignment analysis of the 950-base marker sequence using BLAST-N revealed 100% homology with L. monocytogenes. The primers designed using the Primer 3 Plus design software had good specificity with acceptable melting temperatures and GC content except that of possible formation of secondary structures.